2016
DOI: 10.1016/j.healun.2016.01.1231
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in outcomes after heart transplantation: A systematic review of contributing factors and future directions to close the outcomes gap

Abstract: The demographics of patients undergoing heart transplantation in the United States have shifted over the last 10 years, with an increasing number of racial and ethnic minorities undergoing heart transplant. Multiple studies have shown that survival of African American patients after heart transplantation is lower compared with other ethnic groups. We review the data supporting the presence of this outcome disparity and examine the multiple mechanisms that contribute. With an increasingly diverse population in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 61 publications
3
67
0
Order By: Relevance
“…Our study showed that in the TPE‐treated cohort, both females and Blacks/African Americans were disproportionately increased. These findings are consistent with other studies that suggest that female sex is a risk factor for both AMR and decreased survival and that Black/African American race is associated with decreased survival . Although females and African Americans were overrepresented in the TPE cohort, in our statistical model, race and sex were not found to be associated with survival (Table ).…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that in the TPE‐treated cohort, both females and Blacks/African Americans were disproportionately increased. These findings are consistent with other studies that suggest that female sex is a risk factor for both AMR and decreased survival and that Black/African American race is associated with decreased survival . Although females and African Americans were overrepresented in the TPE cohort, in our statistical model, race and sex were not found to be associated with survival (Table ).…”
Section: Discussionsupporting
confidence: 92%
“…Other suggested factors predicting inferior outcomes among AAs include pretransplant dialysis vintage, which is a known risk factor for reduced patient and graft survival, lower income, reduced access to healthcare, more comorbid conditions, and higher medical nonadherence [29]. It is well-established that AAs are disproportionately affected by hypertension, diabetes, and obesity, compared to CAs, which increases their coronary heart disease risk [30] and hence negatively impacts posttransplant outcomes [31]. In addition, posttransplant outcomes in AAs may potentially be impacted by nonadherence to medications.…”
Section: Disparities In Posttransplant Outcomes Among Aasmentioning
confidence: 99%
“…As discussed in a recent review, this racial disparity may be explained by individual-level psychosocial, immunological, and genetic factors not reflected in conventional measurements of socioeconomic advantage. 39 …”
Section: Discussionmentioning
confidence: 99%